Separating the wheat from the chaff – towards a taxonomy of open innovation - Duarte, Vanessa (2012)
Purpose – The main objective of our work is to shed light on the confusion of terminologies related to open innovation through the development of an open innovation taxonomy. By analyzing published case studies using numerical taxonomy methods, we propose a taxonomic classification of open innovation. Design/methodology/approach – We first review earlier work on firm collaboration and concepts related to open innovation in order to understand the main motivations and conditions behind open innovation- like strategies. We then proceed to collect and systematically analyze twenty published case studies, and using numerical taxonomy methods we produce a taxonomic classification of open innovation. As a first approach to taxonomy on open innovation strategies, the UPGMA methodology used seems very promising. The taxonomy of open innovation developed here can also be used as a decision making tool through the comparison of open innovation strategies inherent in the taxonomy. Findings – Through the numerical taxonomy analysis we have been able to objectively create groups of similar cases, and strategies therein. This paper is able to draw some interesting conclusions by identifying two general strategies of collaboration- a free revealing ―democratic‖ strategy and a formal collaboration strategy. The first involves a proliferation of partners whose technical and creative skills are specific to the industry and the source of knowledge, and where the degree of interaction, play an important role. The second broad strategy of cooperation is linked to more formal collaboration, generally firm-firm collaboration; in this group we found a large focus on markets features, especially technological intensity. Research limitations/implications – This is a first attempt to use numerical taxonomy for the classification of open innovation strategies. A limited number of case studies were used to permit an intuitive understanding of the taxonomy, however inclusion of more studies would provide robustness to the conclusions. Within each of the two broad open innovation strategies, exist more specific strategies, which should be further analyzed in future research and the taxonomy should create nomenclature or archetypes of open innovation strategies. Practical implications – The taxonomic classification of types of open innovation based on characteristics of firms and their environment allows the use of a classification grid to provide strategic orientation to firms wishing to pursue open innovation-like strategies. Originality/value – This paper adds objectivity to the research of different open innovation strategies by using a method developed in the natural sciences. Based on a systematic review of literature, we were able to identify key characters describing features and come up with a taxonomy of open innovation, which goes a significant way to making sense of the plethora of terminology related to open innovation. Key features of different open innovation strategies are also revealed.